Study on the synergy of Theatre Pedagogy and Philosophy for Children: A multi-disciplinary approach - Mamali, Evi; Papadopoulos, Simos (Epistēmēs Metron Logos, 2021)
This study explores the reasons why theatre pedagogy as practiced through drama inquiry is highly compatible with philosophical inquiry as practiced in a community of inquiry. After clarifying the way in which theatre and philosophy can be practiced in an educational context, common elements of drama and philosophical inquiry are examined in terms of epistemology and method. As it is suggested that a number of skills and attitudes can be traced in both drama and philosophical inquiry, there follows an elaborated presentation of such points of relevance. The study concludes that a synergy of drama and philosophical inquiry may not only be feasible but also highly productive as there are common aims and principles which provide a basis for applying effectively a model of philosophical inquiry assisted by drama inquiry.